Healthy homes reducing the entry of electromagnetic waves (LACCEI, 2024)
In recent years we have been involved in a controversy regarding electromagnetic waves such as the famous 5G waves, which for some brings benefits such as high speed data transfer for the Internet, however, recent studies in highly developed countries warn about the consequences that these could bring to human health. That is why the main objective sought with this research is to be able to reduce the passage of electromagnetic waves in homes and thus they can be clean of electromagnetic noise. Being a novel study in our region, we will announce our positive results and with this we could extend its application to our entire country and thus become an option for housing construction, improving people's quality and comfort of life. This application will not only bring benefits to human health but also protect our electrical devices from different failures, thus extending their useful life. To achieve our objective, we base ourselves on the principle of the Faraday Cage, which proves that on a surface closed with a metallic material, the electromagnetic field is null, so we apply this principle to a home, for this I use the construction of a model of a house to scale, to be able to carry out the respective tests, thus being able to quantify the reduction of electromagnetic waves. For this investigation I will use aluminum foil as the main material that will simulate aluminum sheets thus covering my structural elements and walls, thus shielding the house. For the open surfaces such as doors we would use aluminum doors, and for the windows a glass against the protection of electromagnetic waves which can already be found in the market in countries like Spain, which have already taken a lot of interest in these issues. All materials preferably must be connected to a ground to avoid creating electric fields due to electrical installations. The results were very favorable for the tests of the shielding of structural elements with aluminum, therefore, we could put it into practice at the level of construction of a real house, which I will detail its construction process later.